ИННОВАЦИОННО-ИНВЕСТИЦИОННЫЕ НАПРАВЛЕНИЯ РАЗВИТИЯ И СОВЕРШЕНСТВОВАНИЯ ТЕХНОЛОГИЧЕСКИХ СХЕМ ПРОИЗВОДСТВА РАФИНИРОВАННЫХ МАРГАНЦЕВЫХ ФЕРРОСПЛАВОВ (Modern Problems of Metallurgy, 2020)
The analysis of modern production of refined manganese ferroalloys and the basic directions of its perfection is carried out. It is shown that the main trend of development of this direction is based on the introduction of technological schemes for refining melts by purging in converters or by traditional methods of mixing them with oxide melts and their intensification by increasing the area of ​​contact of reacting components due to their intensive mixing or purging with inert gases. The technological scheme, the equipment of its characteristics (the supplier - the company Sinosteel JEMECO (China)), for the plant for the production of metallic manganese by the silicothermic method is given.
Keywords: manganese metal, project, refining, technological scheme, furnace parameters, lining, current lead, ecology.